Responses of the Ethiopian fruit fly, Dacus ciliatus (Diptera, Tephritidae) to colored rectangles, spheres, and ovoids - Vayssières, Jean-François; Dal, F. (2004)
On the Mascarene Islands, the Ethiopian fruit fly, Dacus ciliatus Loew, is one of the major frugivorous pests of Cucurbitaceae. Both visual and olfactory signals involved in the host location process need to be evaluated to better understand the behaviour of this species, and to improve trapping. This article reports results of our studies with visual stimuli. Responses of immature and sexually mature females and males were studied in two outdoor field cages. The reaction of cohorts of 150 adults of each sex to coloured rectangles, spheres and ovoids of different sizes were observed during four successive days within a period of 13 weeks. Sexually mature males were caught more frequently than females of the same age. Captures rates were high: more than 70% for females and more than 80% for males. Spherical shapes were preferred by both sexes toovoid and rectangular shapes. Orange colours were the most attractive to sexually mature females, whereas yellow colours were the most attractive to sexually mature males. Immature females preferred yellow colours.